"Lascolabacillus massiliensis": a new species isolated from the human gut. (May 2016) - Beye, M.; Bakour, S.; Traore, S.I.; Raoult, D.; Fournier, P.-E.
Abstract: We report here the main characteristics of " Lascolabacillus massiliensis " strain SIT8 (CSUR P1560) that was isolated from the stool of a healthy 28-month-old boy.